2022
DOI: 10.1371/journal.ppat.1010218
|View full text |Cite
|
Sign up to set email alerts
|

Revealing spatio-temporal dynamics with long-term trypanosomatid live-cell imaging

Abstract: Trypanosoma brucei, the causative agent of human African trypanosomiasis, is highly motile and must be able to move in all three dimensions for reliable cell division. These characteristics make long-term microscopic imaging of live T. brucei cells challenging, which has limited our understanding of important cellular events. To address this issue, we devised an imaging approach that confines cells in small volumes within cast agarose microwells that can be imaged continuously for up to 24 h. Individual T. bru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…(C) To explore potential passive and active trap invasion, we chemically fixed T. brucei parasites to investigate their distribution after influx into the chip both as a single influx, and upon double influx. While on average, 75% of traps were invaded by untreated 2913 parasites, only 16.2% of traps had parasites present if the here is complementary to various other valuable methods that have been generated over the last decade, to study various aspects of T. brucei behaviour [13,15,18,19,[30][31][32][33] reviewed in [12]. We divide these methods into 6 groups for further discussion: a) temperature-based, b) chemical-adhesion-based, c) gel-based, d) optical traps; e) droplet-based and f) microfluidics and nanopatterning.…”
Section: Technical Features: Strengths and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(C) To explore potential passive and active trap invasion, we chemically fixed T. brucei parasites to investigate their distribution after influx into the chip both as a single influx, and upon double influx. While on average, 75% of traps were invaded by untreated 2913 parasites, only 16.2% of traps had parasites present if the here is complementary to various other valuable methods that have been generated over the last decade, to study various aspects of T. brucei behaviour [13,15,18,19,[30][31][32][33] reviewed in [12]. We divide these methods into 6 groups for further discussion: a) temperature-based, b) chemical-adhesion-based, c) gel-based, d) optical traps; e) droplet-based and f) microfluidics and nanopatterning.…”
Section: Technical Features: Strengths and Future Directionsmentioning
confidence: 99%
“…Main methods have been reviewed by Muthinja et al ([12]), and include elastic substrates which allow for the measurement of force transmission during cell migration [13]; nano-and micro-patterns, which can serve as binding sites for motile parasites [14]; micro-pillar arrays that allowing for parasite navigation studies [13]; micro-channels, which have aimed at confining parasites for longitudinal visualization [15]; and organs-on-chip, which have aimed at the replication of in vivo parameters for the study of host-parasite interactions (reviewed in [16,17]). A recent device incorporated encapsulation and cultivation of single parasites in emulsion droplets to investigate parasite growth patterns and parasite population heterogeneity [18,19]. While each of these devices comes with specific strengths, with our work we address one common limitation to all: the possibility to maintain free-swimming parasites (single and collective) in the field of view and image them for long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the size difference between the two daughter cells produced during T. cruzi epimastigote cell division, it is possible that there would be a difference in their cell division rates during their subsequent round of division. We recently developed a strategy using agarose microwells that allows us to confine and image trypanosomatids in small volumes without immobilization, which permits the parasites to divide at rates similar to those in bulk cultures [72]. During optimization of our microwell approach for imaging T. cruzi epimastigotes, we found that increasing the height of the wells to 6 microns to account for the width of T. cruzi epimastigote cells undergoing cytokinesis provided unimpeded cell divisions, with no loss in viability out to 48 h. We isolated single cells in wells and monitored them until they divided, then tracked the subsequent division rate of the daughter cells (Fig 9A and S1 Movie).…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…PDMS stamps and agarose microwells were fabricated as previously described, for a final concentration of 3.5% SeaPlaque agarose (Lonza, Basel, Switzerland) in LDNT media [72]. Microwell dimensions used in these studies were 50×50×6 μm.…”
Section: Generating Agarose Microwellsmentioning
confidence: 99%
“…A recent device incorporated encapsulation and cultivation of single parasites in emulsion droplets to investigate parasite growth patterns and parasite population heterogeneity [18,19]. While each of these devices comes with specific strengths, with our work we address one common limitation to all: the possibility to maintain free-swimming parasites (single and collective) in the field of view and image them for long periods of time.…”
Section: Introductionmentioning
confidence: 99%